Effect of Land Use on Runoff Water Quality in Sulaimani Governorate/ Kurdistan Region, Iraq. - Barzinji, Khalid Taiyb Muhammad; Ahmad, Ali Bawashekh (Sulaimani Journal for Pure and Applied Sciences, 2017)
This study presents an assessment of the quality of rainfall and runoff water, at the studied area based on analysis of three rainfall storms representing two consecutive years (2013 - 2014). The aim of this research paper was to identify whether the rainfall and runoff water quality had been influenced by the land use in Sulaimani governorate. The rainfall and runoff water quality were determined by comparing their chemical composition of major cations and anions with maximum permissible limits for water consumption and irrigation use. Analysis of PHreaction, temperature, electrical conducting, total dissolved solids, were done. Results showed that, values of electrical conductivity, total dissolved solids, took the highest values in forest land use for the first storms and took the highest values in asphalt land use in case of the two other storms. It also showed that the major ion contents show the trend Ca+2 > Mg+2 >K+>Na+ except asphalt land use where Na+ was more than K+, while anion composition follow the trend SO=4 > HCO-3>Cl-> NO=3>PO≡4 except asphalt land use where Cl- was more than HCO3-. The results appeared that the runoff water of the studied area are found to be unsuitable for domestic use according to Water Quality Index(WQI), while all runoff water samples from the studied land uses were suitable for the purpose of irrigation according to Irrigation water Quality Index,(IWQI).
Keywords: Land use; Runoff; Water quality; Sulaimani Governorate